2020
DOI: 10.1021/acs.orglett.0c00917
|View full text |Cite
|
Sign up to set email alerts
|

Superelectrophilic Fe(III)–Ion Pairs as Stronger Lewis Acid Catalysts for (E)-Selective Intermolecular Carbonyl–Olefin Metathesis

Abstract: An intermolecular carbonyl−olefin metathesis reaction is described that relies on superelectrophilic Fe(III)-based ion pairs as stronger Lewis acid catalysts. This new catalytic system enables selective access to (E)-olefins as carbonyl−olefin metathesis products. Mechanistic investigations suggest the regioselective formation and stereospecific fragmentation of intermediate oxetanes to be the origin of this selectivity. The optimized conditions are general for a variety of aryl aldehydes and trisubstituted ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 49 publications
2
8
0
Order By: Relevance
“…The compound was obtained as colorless oil: 43.2 mg, 0.22 mmol, 90%. The spectral data matches with the one reported in the literature …”
Section: Methodssupporting
confidence: 88%
See 1 more Smart Citation
“…The compound was obtained as colorless oil: 43.2 mg, 0.22 mmol, 90%. The spectral data matches with the one reported in the literature …”
Section: Methodssupporting
confidence: 88%
“…The spectral data matches with the one reported in the literature. 24 1 H NMR (300 MHz, CDCl 3 ): δ = 7.58−7.43 (m, 2H), 7.28−7.20 (m, 1H), 7.10−7.02 (m, 1H), 6.74 (dd, J = 15.7, 1.8 Hz, 1H), 6.19 (dq, J = 15.6, 6.7 Hz, 1H), 1.93 (dd, J = 6.6, 1.8 Hz, 3H); 13 C{ 1 H} NMR (75 MHz, CDCl 3 ): δ = 137. 7, 132.8, 129.9, 128.8, 128.0, 127.3, 126.8, 123.0, 18.7. But-2-en-1-ylbenzene (2g).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…However, MeCN still gave better result, and less polar solvents were found to be not suitable in this reaction, probably because low polar solvents enhance the coordination of a counter anion to the radical cation intermediates, leading to the decreased reactivity. Next, we used cationic silver salts as an additive to cause chloride abstraction from FeCl 3 to generate reactive iron(III) species [16] . After screening several silver salts, we found that AgSbF 6 shows high efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we used cationic silver salts as an additive to cause chloride abstraction from FeCl 3 to generate reactive iron(III) species. [16] After screening several silver salts, we found that AgSbF 6 shows high efficiency. As a result, the cycloadduct 3 e was obtained in 90% yield by using 10 mol% of FeCl 3 and 30 mol% of AgSbF 6 (entry 7).…”
mentioning
confidence: 97%
“…Recent reports from Schindler et al have described the activation of iron-based catalysts by a mechanism similar to superelectrophilic activation [ 13 , 14 ]. In carbonyl-olefin metathesis reactions, kinetic studies have suggested the formation of dimeric complexes of FeCl 3 , which enhance the electrophilic reactivity of the iron center and promotes this remarkable transformation ( Scheme 2 ).…”
Section: New Types Of Superelectrophilesmentioning
confidence: 99%